Strategi Konseling untuk Menjembatani Perbedaan Pilihan Karier antara Siswa dan Orang Tua: Counseling Strategies to Bridge Differences in Career Choices between Students and Parents - Edil Wijaya Nur; M. Amirullah (Litera Academica Publishing, 2025)
The conflict between students and parents in choosing an academic major is a common phenomenon, especially in collectivist cultures where family expectations significantly influence educational decisions. This study aims to explore various psychology-based career counseling approaches to bridge the perspective gap between students and parents. Using a literature review method, this research analyzes different theories, such as Social Cognitive Career Theory (SCCT), Career Construction Theory (CCT), Adolescent-Parent Career Congruence (APCC), and Self-Determination Theory (SDT), in the context of academic decision-making. The findings indicate that alignment between students' aspirations and parental expectations can be achieved through exploratory support rather than coercive approaches. Furthermore, counseling models that provide space for students to develop autonomy in decision-making have been proven to enhance their career readiness and satisfaction. This study recommends implementing counseling strategies that facilitate effective communication between students and parents, as well as incorporating more adaptive psychological approaches in career guidance programs in schools.